To the estimation of the workload of the student's individual work in the competent approach - Mikhail I. Umansky (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Individual work of students (ISW) is an integral part of the educational process. Formally, the volume of individual work is established by the curricula. On the examples of majors 38.03.01, 38.03.02, it is shown that the existing planning of the ISW is not rational. In the context of continuous reform of the educational process, it is extremely difficult to find the optimal ratio of the content of assignments for the formation of competences and the complexity of these tasks. In order to reduce the unreasonable expenditure of time for the implementation of the ISW, it is suggested to monitor the workload of students, to use educational and methodological materials to form effective technological skills and tasks performance, and to promote self-study planning skills from the first semester.